2020
DOI: 10.1093/eurheartj/ehaa652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of icosapent ethyl on progression of coronary atherosclerosis in patients with elevated triglycerides on statin therapy: final results of the EVAPORATE trial

Abstract: Aims Despite the effects of statins in reducing cardiovascular events and slowing progression of coronary atherosclerosis, significant cardiovascular (CV) risk remains. Icosapent ethyl (IPE), a highly purified eicosapentaenoic acid ethyl ester, added to a statin was shown to reduce initial CV events by 25% and total CV events by 32% in the REDUCE-IT trial, with the mechanisms of benefit not yet fully explained. The EVAPORATE trial sought to determine whether IPE 4 g/day, as an adjunct to diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
182
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(216 citation statements)
references
References 35 publications
8
182
0
1
Order By: Relevance
“…Several studies using intra-coronary imaging showed that circulating EPA levels were associated with lipid plaque volume, [ 24 ] and fibrous-cap thickness of the plaque [ 25 ]. A randomized control study evaluating coronary plaque change by multidetector computed tomography showed that treatment with n-3 PUFA formulation for 18 months significantly reduced the accumulation of low-attenuation plaque, which is a component of vulnerable plaque, compared to placebo [ 26 ]. Furthermore, a recent study showed that the proportion of EPA in serum phosphatidylcholine at the time of ACS was associated with further clinical adverse events [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using intra-coronary imaging showed that circulating EPA levels were associated with lipid plaque volume, [ 24 ] and fibrous-cap thickness of the plaque [ 25 ]. A randomized control study evaluating coronary plaque change by multidetector computed tomography showed that treatment with n-3 PUFA formulation for 18 months significantly reduced the accumulation of low-attenuation plaque, which is a component of vulnerable plaque, compared to placebo [ 26 ]. Furthermore, a recent study showed that the proportion of EPA in serum phosphatidylcholine at the time of ACS was associated with further clinical adverse events [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Icosapent ethyl represents high‐dose, purified eicosapentaenoic acid that showed promising results in the recent trials 5–8 . The REDUCE‐IT trial enrolled 8,179 patients who were followed for a median of 4.9 years 5 .…”
Section: Referencementioning
confidence: 99%
“…Some of them could be (i) antiplatelet effect that could be responsible for higher percentage of bleeding among patients who used this medication; (ii) anti‐inflammatory mechanism reflected in significant reduction of hsCRP in the icosapent ethyl group; and (iii) stabilization and/or regression of coronary atherosclerotic plaque. The later mechanism was investigated in the separate EVAPORATE trial that provided some answers, but also raised many questions 7,8 …”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In this commentary, we summarized the most important trials presented during the 2020 Virtual ESC Congress (Table 1) which we predict will improve our everyday clinical practice [12][13][14][15][16][17][18][19][20][21][22][23][24]. The EMPEROR-Reduced (EMPagliflozin outcomE tRial in Patients With chrOnic heaRt Failure With Reduced Ejection Fraction) trial [23] further strengthened the positive findings observed in the DAPA-HF (Study to Evaluate the Effect of Dapagliflozin on the Incidence of Worsening Heart Failure or Cardiovascular Death in Patients With Chronic Heart Failure) trial [25].…”
mentioning
confidence: 99%